Climate-Related Gradients On Vegetation Diversity Of The Altai-Sayan Orobiome (Southern Siberia) - Maxim V. Bocharnikov (Geography, Environment, Sustainability)
An analysis of the spatial organization of vegetation cover has been carried out for the Altai-Sayan orobiome in connection with climatic conditions in the Southern Siberian mountains based on original relevés of plant communities at the 4 altitudinal spectra. Basic bioclimatic parameters on the altitudinal spectra of vegetation have been determined according to latitudinal and longitudinal differentiation of climate. Correlation and discriminate analyses allowed to identify the regional features of altitudinal gradients in species diversity of the spectra as well as the role of parameters in the structure of typological diversity of vegetation for belts of high-mountain tundra, alpine and subalpine meadows and sparse forests, dark coniferous mountain taiga forests, chern-taiga forests, small leave – light coniferous subtaiga forests, forest-steppe. A compiled bioclimatic scheme characterizes the spatial organization of orobiome’s vegetation by basic bioclimatic parameters on the regional level (continentality index, average temperature of January). This scheme shows regional features of the diversity of vegetation in Southern Siberia, in adjacent plain and mountain regions according to climatic conditions. Identified patterns determine unity of the Altai-Sayan orobiome as well as regional differentiation that reflected on the development of types of vegetation zonality. They can be used to analysis of vegetation forming in different mountain systems.